PENINGKATAN KUALITAS AMPAS SAGU MELALUI FERMENTASI SEBAGAI BAHAN PAKAN TERNAK - I. Martaguri; Mirnawati Mirnawati; H. Muis (Jurnal Peternakan, 2011)
The aim of this research was to improve the nutrient of sago waste through fermentation with various microbescombination, inoculum dosage and fermentation length. The experiment used complete randomized design (CRD) with3x3x3 factorial and twice repetition. The first factor was three kind of microbe (A): (1) Neurospora sp (2) Pennicillium sp,(3) Trichoderma harzianum. The second factor was inoculume dosage (B): (1) 3%, (2) 6%, and (3) 9%. The third factorwas fermentation length (C): (1) 4 day, (2) 7day and (3) 10 day. The parameters were dry matter, crude protein and crudefiber. The results of study showed that there were no significant (P>0.05) interaction between factor A, B and C, than factorA and B, factor A and C, factor B and C, to dry matter, crude protein and crude fiber of fermented sagos waste. But everyfactor A, B and C were significantly (P<0.01) affected to dry matter, crude protein and crude fiber of fermented sagos waste.The conclusion was sagos waste which was fermented by Pennicillium sp, inoculume dosage 9% andfermentation length 10 day showed a better content. This condition can be seen in dry matter 64.21%, crudeprotein 14.08%, and crude fiber 13.67%